ANALISIS KOMPILASI HUKUM ISLAM TENTANG TOLOK UKUR HIBAH YANG DIPERHITUNGKAN SEBAGAI WARISAN - Rahmita, Naviri Masma; Budiono, Rachmad (Jurnal Cakrawala Hukum, 2017)
Article 211 The Compilation of Islamic Law describes grants from parents to their children. The issues studied are what benchmarks grants from parents to their children can be counted as inheritance and what are the benchmarks of grants from parents to their children accounted for as grants. This research uses Legislation Approach with normative research type. The legal material of this research is primary, secondary and tertiary legal material. The results that can be concluded in the study of this journal are all gifts that parents give to their children that are not related to the cost of childcare, whether physical growth, spiritual and that pertains to the child's education then the gift is considered as an inheritance. While the benchmark of grants from parents to their children is taken into account as grants are all grants given to parents of parents to their children either giving related to the cost of childcare and education of children as well as gifts that are not related to the maintenance of children and also the education of children, whose nature does not expect the reward of the gift, then the gift is taken into account as a grant.